The Bell Lake group and Anton Complex: a basement – cover sequence beneath the Archean Yellowknife greenstone belt revealed and implicated in greenstone belt formation - Isachsen, C. E.; Bowring, S. A. (Canadian Journal of Earth Sciences, 1997)
U–Pb zircon and monazite geochronology indicates the presence of a >2.93 Ga basement (Anton Complex) and >2.8 Ga cover sequence (Bell Lake group) beneath the 2.70 to >2.72 Ga Kam Group of the Yellowknife greenstone belt in the southern Slave Province. The Bell Lake group comprises remnants of a quartzite – rhyolite – banded iron formation succession. The ages of detrital zircons from the quartzite unit constrain its deposition to be younger than 2.92 and range up to 3.7 Ga. U–Pb ages for gneisses beneath the Bell Lake group are in excess of 2.93 Ga and they are locally overlain by the quartzite. The contact between the tholeiitic to calc-alkaline Kam Group and the Bell Lake group is poorly exposed and equivocal. Approximately 6 km higher in the section, the Ranney chert, a felsic volcaniclastic layer, separates 2.70 – 2.72 Ga tholeiitic to calc-alkaline upper Kam Group rocks from a lower tholeiitic section containing sheeted-dike complexes. Zircons from the Ranney chert yield Pb –Pb ages ranging from 2.72 to >2.8 Ga. The older ages suggest proximity of older basement during deposition of mostly tholeiitic lower Kam Group volcanic rocks in an extensional setting, followed by deposition of the upper Kam Group, which is more arc-like in character, on this earlier-formed tholeiitic crust beginning at 2.72 Ga.